SAT0203 Autologous Fat Transfer for Digital Ulcers Treatment in Systemic Sclerosis. (23rd January 2014) - Pozzi, M. R.; Allevi, E.; Donati, C.; Erba, G.; Riva, M.; Valena, C.; Mazzola, I.; Del Bene, M.
Abstract : Background: Digital ulcers (DUs) occur in up to 50% of patients with Systemic Sclerosis (SSc). DUs are painful and lead to disability. DUs are more or less extended, often multiple, with chronic course, able to influence quality of life and frequently recurrent. Management of DUs includes pharmacologic and local therapy:the healing is slow and the ulcer can become infected or evolve to gangrene. Autologous fat grafting(AFG) is a technique used in recostructive surgery to promote repair of soft tissues: the effect is probably due to the Adipose-derived stem cells (ASCs) contained in the fat. Objectives: We used AFG to treat DUs refractory to conventional treatment to enhance healing. Methods: We treated 9 SSc patients with 15 refractory DUs. All were treated with iv Iloprost:8 pts were treated with CCB, 4 with bosentan, 2 with sildenafil and 7 with low dose aspirin. The local treatment included debridment, moist dressing and dermal substitutes. The Coleman technique was used for AFG: the purified fat tissue was injected on the border and beneath the larger ulcers or at the finger base for the smaller DUs. Results: The ulcers treated were ischemic;one was a traction ulcer. Then were on the hands, 3 on the feet and 2 on the legs. The AFG was done 2 to 8 months since the ulcer onset. No improvement was observed in 2 pts: all the 3 ulcers were on the feet and peripheral arterial disease was present. In 10 ulcers the outcome was positive with complete healing in 8 to 12 weeks: size reduction of ≥ 50% was obtained in 2 DUs. In all but two pts in which the procedure was ineffective, the pain improved allowing a reduction of analgesic therapy. Until now we did not observe DUs recurrence in the same site. Conclusions: The DUs represent a challenge in SSc and the optimal therapeutic strategy is not jet defined. Stem cell therapy has emerged as an approach to accelerate wound healing, but it is not available in clinical practice. ASCs are the precursor cells contained within the stromal-vascular fraction of fat tissue. Experimental data suggest that ASCs contribute to cutaneous regeneration and participate in new vessels formation. ASCs secret angiogenic cytokines including VEGF, HGF and FGF2, which increase neovascularization and enhance wound healing in injured tissues: those functions are enhanced by hypoxia through upregulating secretion of growth factors. The AFG is used in reconstructive surgery and enables repair of soft tissue:the technique is quite simple and minimally invasive, with low associated morbidity. Although there is no overlap between AFG and ASCs therapy, the role of ASCs in fat grafting survival and improvement of surrounding tissues seems to be crucial. The tissutal chronic ischemia and the impairment of vasculogenesis, leading to tissue loss in SSc, could potentially benefit from new vessels formation and cutaneous regeneration induced by ASCs contained into the fat. In this preliminary study the AFG was able to shorten the ulcer healing time, reduce the need of pharmacological and local therapy and improve pain in the majority of the cases. Although we have to take into account the contribution of vasodilator therapy and appropriate wound dressing, nevertheless we have shown the potential role of a simple method to exploit the regenerative potential of autologous fat in SSc ulcers repair. Disclosure of Interest: None Declared